Self-Regulated Learning Practice of Undergraduate Students in Health Professions Programs - Chitra, Ebenezer; Hidayah, Norul; Chandratilake, Madawa; Nadarajah, Vishna Devi (Frontiers in Medicine, 2022)
Background University students are expected to take charge of their learning without being dependent on teachers. Self-regulated learning (SRL) is the process by which students direct their learning to achieve their set targets and goals in a timely and controlled manner. This study was undertaken to explore the practice of SRL by undergraduate students from different programs in a health science focused university during COVID-19 pandemic. Method Thirty-three undergraduate students of five health professions education programs were recruited to take part in focus group discussions to explore their SRL practice with online learning. Their responses were subjected to thematic analysis. Result Our students appeared to practice SRL, going through the phases of forethought and goal setting, performance and self-reflection. They set goals for academic as well as personal development in the university. Academic goals like achieving target GPA or marks were achieved by following different study techniques, personal management including time management, and by creating a conducive learning environment. Personal development such as interpersonal skills, social networking was achieved through socializing and participating in extracurricular activities. The students also engaged in self-reflection and analysis of their own performance followed by designing strategies to manage the challenges they faced. Conclusion Undergraduates of health professions programs appear to show evidence of practicing SRL. Although impacted by COVID-19 induced lockdown and online learning, they seem to have strategized and achieved their goals through individualized SRL processes. Promoting and fostering an atmosphere of SRL in universities to cater to the needs of the students would help them be more successful in their careers.